PENENTUAN DISTRIBUSI INDUKSI MAGNETIK YANG DITIMBULKAN OLEH BERBAGAI JENIS TELEPON SELULER DENGAN MENGGUNAKAN PROBE MAGNETIK PASCO - Herianto '; Erwin '; Mbantun Ginting (Jurnal Online Mahasiswa (JOM) Bidang Matematika dan Ilmu Pengetahuan Alam, 2014)
The distribution of induced magnetic field due to various kinds of cellular telephone has been investigated. The induced magnetic field was measured using Magnetic Probe Pasco in two directions namely horizontal dan vertical. In horizontal direction the induced magnetic field was measured with the distance of 0,5 cm above the cellular telephone. The result showed that the widest distribution of magnetic field was generated by Sony Ericcson cellular telephone, while Samsung cellular telephone generated the narrowest value of induced magnetic field. Moreover, the highest and lowest value induced magnetic field were generated by Sony Ericcson and Sony were 2,4x10-3Tesla and 1,2x10-3Tesla respectively. In vertical direction, the induced magnetic field was reduced significantly the as measured away from the cellular telephone. The value of magnetization was highest from Samsung cellular telephone and the lowest from Blackberry. The value of magnetization from Samsung and Blackberry was 9,26x10-5emu/cm3 and 7,16x10-5emu/cm3 , respectively.